Technical note: Removing dynamic sea-level influences from groundwater-level measurements - P. Haehnel; T. C. Rasmussen; G. C. Rau (Hydrology and Earth System Sciences, 2024)
The sustainability of limited freshwater resources in coastal settings requires an understanding of the processes that affect them. This is especially relevant for freshwater lenses of oceanic islands. Yet, these processes are often obscured by dynamic oceanic water levels that change over a range of timescales. We use regression deconvolution to estimate an oceanic response function (ORF) that accounts for how sea-level fluctuations affect measured groundwater levels, thus providing a clearer understanding of recharge and withdrawal processes. The method is demonstrated using sea-level and groundwater-level measurements on the island of Norderney in the North Sea (northwestern Germany). We expect that the method is suitable for any coastal groundwater system where it is important to understand processes that affect freshwater lenses or other coastal freshwater resources.